The impact of foreign direct investment and technical change on regional growth - George Korres; Theodoros Iosifides (European Regional Science Association (ERSA), 2002)
Research and Development (R&D) and technical change are both directly related to industrial infrastructure conditions, modernization process, productivity levels, regional and socio-economic growth. Technological change caused by Foreign Direct Investments (FDIs) usually widens the socio-economic gap and divergence between different regions (concentration effect), whereas technological imitation, transfer and diffusion tend to enhance regional convergence and cohesion (diffusion effect). This paper attempts to investigate the relation between FDIs, technical change and regional growth. Additionally, it aims to estimate the impact of technical change generated by FDIs on regional growth, and uses an empirical model and available data at regional level.
Keywords: 330